2023
DOI: 10.30935/cedtech/12918
|View full text |Cite
|
Sign up to set email alerts
|

The effects of TPACK and facility condition on preservice teachers’ acceptance of virtual reality in science education course

Abstract: Virtual reality (VR) is developing in line with the establishment of the learning metaverse, although the relationship between its acceptance and technological pedagogical content knowledge (TPACK) is very unclear. Therefore, this study aims to determine the effects of facility condition (FC), technological acceptance model (TAM), and TPACK on pre-service teachers’ use of VR in Indonesian science education courses. This condition emphasizes the description of these teachers’ readiness in designing VR for learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…Other studies that support the results of the work, primarily in terms of using the metaverse in all areas of life including education, by offering solutions to possible problems and promoting the use of the metaverse in technology-oriented educational environments for sustainable and quality education, based on applications like the metaverse etc., primarily benefitting from the metaverse and more specifically the use of technology and the internet, university, class, age, and gender (Parsons et al, 2019;Ning et al, 2021;Fitria et al, 2022;Hwang & Chien, 2022;Kerneža & Kordigel Aberšek, 2022;Kuloğlu et al, 2022;Lin et al, 2022;Yoleri & Anadolu, 2022;Zhang et al, 2022;Buchner & Kerres, 2023;Chua & Yu, 2023;Deng & Matthes, 2023;Gürkan & Bayer, 2023;Thohir et al, 2023), appear to be in harmony with the study results.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies that support the results of the work, primarily in terms of using the metaverse in all areas of life including education, by offering solutions to possible problems and promoting the use of the metaverse in technology-oriented educational environments for sustainable and quality education, based on applications like the metaverse etc., primarily benefitting from the metaverse and more specifically the use of technology and the internet, university, class, age, and gender (Parsons et al, 2019;Ning et al, 2021;Fitria et al, 2022;Hwang & Chien, 2022;Kerneža & Kordigel Aberšek, 2022;Kuloğlu et al, 2022;Lin et al, 2022;Yoleri & Anadolu, 2022;Zhang et al, 2022;Buchner & Kerres, 2023;Chua & Yu, 2023;Deng & Matthes, 2023;Gürkan & Bayer, 2023;Thohir et al, 2023), appear to be in harmony with the study results.…”
Section: Discussionsupporting
confidence: 63%
“…Hence, TSE, TAM as well as IMDM could be fostered. At least for IMDM, we could prove that it significantly increased while working in a makerspace (Max et al, 2023), while the relationship with TSE and TAM has been suggested by other studies (e.g., Joo et al, 2018;Thohir et al, 2023;Wangdi et al, 2023).…”
Section: Z-valuesupporting
confidence: 70%
“…Although there have been numerous studies dealing with the relationships of the various constructs with each other and with TPACK among pre-service teachers and in-service teachers, there is still disagreement about which factors significantly influence TPACK development. In many studies, TPACK serves as the prerequisite for other factors, like TSE or TAM (e. g., Joo et al, 2018;Thohir et al, 2023;Wangdi et al, 2023). The results of this study take another perspective and sharpen the view on the structure of effects influencing the development of TPACK.…”
Section: Z-valuementioning
confidence: 51%
See 1 more Smart Citation
“…The literature on the TPACK framework in the context of VR-based education underscores the importance of a holistic approach to integrating technology into teaching practices [1,5,10]. This entails a balanced amalgamation of CK, PK, and TK, tailored to the affordances of VR technology.…”
Section: Theoretical Background 21 Vr Technology and Tpackmentioning
confidence: 99%